Melanomatose meningea: analise citomorfologica do liquido cefalorraqueano - J. A. Livramento; L. R. Machado; H. A. M. Clemente; A. Tabares-Olives; A. Spina-França (Arquivos de Neuro-Psiquiatria)
Six cases of meningeal melanomatosis are reported. The cytomorphological analysis of cerebrospinal fluid lead to diagnosis in all of them. Emphasis is given to morphological characteristics of the tumor cells and specially to the melanin dark brown pigment, observed in all cases here reported.